2020
DOI: 10.3389/fphar.2020.00515
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Rheumatic Properties of Gentiopicroside Are Associated With Suppression of ROS-NF-κB-NLRP3 Axis in Fibroblast-Like Synoviocytes and NF-κB Pathway in Adjuvant-Induced Arthritis

Abstract: Rheumatoid arthritis (RA) is among the most prevalent forms of autoimmunity. Gentiopicroside (Gent) is an iridoid glucoside derived from the Gentiana Macrophylla Pall which is used in traditional Chinese medicine to treat RA. The present study was designed to explore the ability of Gent to combat RA and to explore the molecular basis for such anti-RA activity both in vitro using tumor necrosis factor alpha (TNF-a)-stimulated human RA fibroblast-like synoviocytes (RA-FLS) and in vivo using a rat adjuvant-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 44 publications
(42 reference statements)
1
24
0
Order By: Relevance
“…The above-described findings indicated that the activities of both NF-κB and NLRP3 are suppressed by KM, which suggests that an upstream regulator of these two signaling pathways might mediate these effects. ROS are signaling intermediates that can drive both NLRP3 inflammasome and NF-κB activation ( Tschopp and Schroder, 2010 ; Wu et al, 2018 ; Wang et al, 2020 ). Herein, we measured production of ROS in marophages stimulated with LPS plus ATP.…”
Section: Resultsmentioning
confidence: 99%
“…The above-described findings indicated that the activities of both NF-κB and NLRP3 are suppressed by KM, which suggests that an upstream regulator of these two signaling pathways might mediate these effects. ROS are signaling intermediates that can drive both NLRP3 inflammasome and NF-κB activation ( Tschopp and Schroder, 2010 ; Wu et al, 2018 ; Wang et al, 2020 ). Herein, we measured production of ROS in marophages stimulated with LPS plus ATP.…”
Section: Resultsmentioning
confidence: 99%
“…AA animals have a quick onset and progression of disease with poly-articular inflammation, which is manifested by increased volume of the hind paw and a typical course of loss of body weight [36].…”
Section: Discussionmentioning
confidence: 99%
“…The arthritis index of these animals was evaluated using a scale of 0 to 4 points, as follows: 0, normal; 1. slight erythema and swelling; 2. moderate erythema and swelling; 3. severe erythema and swelling, limited joint use; 4, deformed claws. 19 The two hind legs both were scored in each rat, with the highest possible score being 8 points. 19 …”
Section: Methodsmentioning
confidence: 99%
“… 19 The two hind legs both were scored in each rat, with the highest possible score being 8 points. 19 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation